Molecular docking and pharmacogenomics of Vinca alkaloids and their monomeric precursors, vindoline and catharanthine - Sertel, Serkan; Fu, Yujie; Zu, Yuangang; Rebacz, Blanka Kamila; Konkimalla, Badireenath; Plinkert, Peter K.; Krämer, Alwin; Gertsch, Jürg; Efferth, Thomas (Biochemical pharmacology, 2011)
Vinblastine and vincristine are dimeric indole alkaloids derived from Catharanthus roseus (formerly: Vinca rosea). Their monomeric precursor molecules are vindoline and catharanthine. While vinblastine and vincristine are well-known mitotic spindle poisons, not much is known about vindoline and catharanthine. Vindoline and catharanthine showed weak cytotoxicity, while vinblastine, vincristine, and the semisynthetic vindesine and vinorelbine revealed high cytotoxicity towards cancer cells. This may reflect a general biological principle of poisonous plants. Highly toxic compounds are not only active towards predators, but also towards plant tissues. Hence, plants need mechanisms to protect themselves from their own poisons. One evolutionary strategy to solve this problem is to generate less toxic precursors, which are dimerized to toxic end products when needed. As shown by in silico molecular docking and biochemical approaches, vinblastine, vincristine and vinorelbine bound with high affinity to α/β-tubulin and inhibited tubulin polymerization, whereas the effects of vindoline and catharanthine were weak. Similarly, vinblastine produced high fractions of mono- and multipolar mitotic spindles, while vindoline and catharanthine did only weakly affect bipolar mitotic spindle formation. Here, we show that vinblastine contributes to cell death by interference with spindle polarity. P-glycoprotein-overexpressing multidrug-resistant CEM/VCR1000 cells were highly resistant towards vincristine and cross-resistant to vinblastine, vindesine, and vinorelbine, but not or only weakly cross-resistant to vindoline and catharanthine. In addition to tubulin as primary target, microarray-based mRNA signatures of responsiveness of these compounds have been identified by COMPARE and signaling pathway profiling.